2018
DOI: 10.18488/journal.11.2018.72.83.92
|View full text |Cite
|
Sign up to set email alerts
|

Organisation Restructuring: The Influence of Interpersonal Conflict, Anomie, and Trust in Management on Counterproductive Work Behaviour

Abstract: Employees" reaction to organization restructuring varies as some react positively towards change but others refuse to accept it. Those who react negatively may engage in counterproductive work behavior. Since the existing studies are scarce in addressing this issue especially during organization restructuring, the present study is meant to investigate the influence of interpersonal conflict, anomie and trust in management on employees" counterproductive work behavior. Data were collected from 215 nonmanagerial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…Oguegbe & Edosomwan's (2021) findings also indicated that organizational trust was negatively correlated with counterproductive work behavior, such as turnover intention. When the organizational trust was maintained, the employees would remain within the organization (Rahim et al, 2018).…”
Section: The Impact Of Organizational Trust On Counterproductive Work...mentioning
confidence: 99%
See 1 more Smart Citation
“…Oguegbe & Edosomwan's (2021) findings also indicated that organizational trust was negatively correlated with counterproductive work behavior, such as turnover intention. When the organizational trust was maintained, the employees would remain within the organization (Rahim et al, 2018).…”
Section: The Impact Of Organizational Trust On Counterproductive Work...mentioning
confidence: 99%
“…Counterproductive work behavior has been conceptualized as negative work behavior and has become one of the interesting research topics (Marcus et al, 2016;Courtois & Gendron, 2017). Additionally, they suggested that other scholars conduct more comprehensive research on counterproductive work behavior that would advance and develop the domains of counterproductive behavior by capturing a more comprehensive range of counterproductive work behaviors and exploring supporting factors to reduce negative actions toward organizations and expand the scope of research such as employing the positive attitude variables which had an impact on counterproductive work behavior, considering that previous studies had been predominated with negative attitudes, or adding control variables to suppress negative organizational behavior (Rahim et al, 2018;Griep et al, 2020). Furthermore, besides choosing exogenous variables, researchers also included a mediating variable of organizational trust, per research conducted by De Jong et al (2016).…”
Section: Introductionmentioning
confidence: 99%
“… 25 Effective, transparent communication is vital at all levels of any organization; however junior and/or new faculty may be especially prone to the deleterious effects of mixed messaging. 26 Faculty productivity, vitality, and mitigation of untoward work outcomes, such as burnout, begin with a successful onboarding process. 27 Academic supervisors should provide clear communication of goals and availability of resources, and keep their word on promises beyond the contract offer.…”
Section: Effective Communication More Common In the Midst Of Health Organizational Cultures And Citizenshipmentioning
confidence: 99%
“…Therefore, additional research is needed to understand the other potential mechanisms through which perceived workplace incivility transforms into employees’ deviant workplace behaviors (Tamunomiebi and Ukwuije, 2021). We argue that workplace incivility results in undermining social relationships and arising interpersonal conflict (Andersson and Pearson, 1999) which, in turn, trigger organizational deviance, employees’ counterproductive workplace behaviors (Rahim et al. , 2018) and withdrawal from the workplace (Wright and Cropanzano, 1998).…”
Section: Introductionmentioning
confidence: 99%